Monitoring Of Wetland Paddy Fields Using Microwave Remote Sensing Data - Abu Bakar, Saiful Bahari (1999)
This thesis contains a study of the relationship between biophysical parameters of the rice fields and radar backscattering coefficients from SAR images. It also studies the images of cultivated rice fields using multi-temporal SAR images. The GlobeSAR program ( a joint project between CCRS and MACRES) was carried out in Malaysia from November 1993 to October 1996. In November 1993, the airborne scatterometer CV-580 SAR was used to collect multi polarized C-band images from the rice paddy in Kedah, Malaysia. From the images it is shown that the HH polarization provides distinct differences in backscattering coefficients from paddy fields at different growth stages. Then we continue to study the capability of monitoring of wetland paddy fields by using the satellite borne RADARSAT SAR images. The approach includes using the RADARSAT Data Standard Mode 7, C- band HH polarized data. Four field measurements were conducted in conjunction with the satellite acquisition which fell on 12th May, 5th June, 29th June and 23rd July 1997. Those dates correspond to different stages of paddy growth, I.e. vegetative phase ( 1st tillering), vegetative phase ( 2nd and 3rd tillering), reproductive phase and ripening phase. There are no distinct row and column effects because the farmers practiced random broadcasting method. Ground measurements were colected which consisted of paddy parameters and moisture, water and soil condition. Two sites were selected: Kampung Tanah Seratus and Kampung Teluk Jawa. Two sets of graphs have been plotted showing the backscatter returns, paddy height above water and plant moisture at diffent growth stages. In the last part of the thesis, the production of the rice mapping for the early rice and late rice is done based on the SAR images. The average difference value of 3 dB is observed between the vegetative stage and reproductive stage. This is chosen as the threshold value in the change detection module in the PCI Easi Pace software. The Kuan Filter ( extended Kuan minimum-mean-square-error filter) is used to reduce the speckle, and ratioing technique is applied in the multi temporal image. The result of rice mapping from the change detection method is compared with the rice map obtained from the Department of Agriculture. The strong match shows that the SAR images have a great potential as a monitoring tool for the paddy field growth stage study.